Biometric Evaluations and Condition Factor of the Mudskipper, Periophthalmus barbarous (Linnaeus, 1766) From Ibaka Mangrove Swamp, Nigeria - Enenwan Precious Udoinyang; Aniefiokmkpong O. Okon; Victoria Folakemi Akinjogunla; Itoro J. Archibong; Unwana J. Effiong; Emmanuel A. Essien (Acta Natura et Scientia)
The length-weight relationship and Fulton condition factor (K) of 404 samples of the mudskipper, Periophthalmus barbarus from Ibaka mangrove swamp were investigated for six months (January to June 2022) using standard methods to accommodate both the dry and wet seasons. For the 404 samples, the mean total length was 11.22±0.11 cm while the mean body weight was 16.4±0.48 g. Other biometric data collected includes percentage eye diameter (ED%) ranging between 5.07 and 8.26 cm for May and February, respectively. Percentage head length (HL%) values were between 20.9 and 28.12 cm for May and January, respectively. For percentage body depth (BD%), the least was recorded in April (19.49 cm) while the highest was observed in February (24.55 cm). The Fulton condition factor (K) determined for most of the sampled months showed that the values were above unity (K>1), indicating good living conditions on account of food availability, absence of parasites/predators, and absence of disease. However, K was less than unity (K<1) in February and June, indicating a possible decline in food availability and other factors responsible for growth. The values of the length-weight relationship (b) were greater than 3 (b>3) in almost all the months except in April, having a value of 2.895, indicating that the species exhibited a positive allometric growth pattern. This implied that as the length of the fish increased, there was also a corresponding increase in the weight of P. barbarus from the Ibaka Mangrove Swamp.